2018
DOI: 10.21620/ijfaas.2017243-48
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Oil Samples Collected from Different Food Points of Multan City of Pakistan

Abstract: Cooking oil has become a part and parcel of modern food system and therefore its safety is of prime significance for health agencies around the globe to ensure good health among the community. Current study was designed to investigate the physicochemical properties including free fatty acids, peroxide value and conjugated dienes; minerals (nickel & cobalt) and heavy metals (lead and cadmium) in oil samples collected from different areas of Multan city of Pakistan. The findings of this study revealed that free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Conjugated diene measurement shows the oxidative stability of the fats or oils in the product which formed by the triplet oxygen or singlet oxygen (Akhtar et al, 2018). Juntachote et al (2007)concluded that storage period reduced the conjugated diene value, but our result shows the opposite.…”
Section: Conjugated Dienes Analysiscontrasting
confidence: 45%
“…Conjugated diene measurement shows the oxidative stability of the fats or oils in the product which formed by the triplet oxygen or singlet oxygen (Akhtar et al, 2018). Juntachote et al (2007)concluded that storage period reduced the conjugated diene value, but our result shows the opposite.…”
Section: Conjugated Dienes Analysiscontrasting
confidence: 45%
“…CD is a measure of the oxidative stability of fats or oils where CD is a lipid hydroperoxide formed by triplet oxygen or singlet oxygen (Akhtar et al, 2018). When the oxidation of lipids progresses, the unconjugated double bonds are converted to conjugated structures that absorb ultraviolet radiations of 233 nm (Peri and Saguy, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Another study also reported that change in the physicochemical properties of the frying oil samples collected from Multan, Pakistan. The results of the study showed that FFA, conjugated dienes, and heavy metals concentrations (cobalt and nickel) were normal, while, peroxide values, Cd, and Pb were more than normal [16]. A recent study conducted in Lahore, Pakistan also reported the quality of fifty frying oil samples being used by SFVs.…”
Section: Introductionmentioning
confidence: 90%